2013
DOI: 10.1371/journal.pone.0054017
|View full text |Cite
|
Sign up to set email alerts
|

Duplication and Diversification of the Spermidine/Spermine N1-acetyltransferase 1 Genes in Zebrafish

Abstract: Spermidine/spermine N1-acetyltransferase 1 (Ssat1) is a key enzyme in the polyamine interconversion pathway, which maintains polyamine homeostasis. In addition, mammalian Ssat1 is also involved in many physiological and pathological events such as hypoxia, cell migration, and carcinogenesis. Using cross-genomic bioinformatic analysis in 10 deuterostomes, we found that ssat1 only exists in vertebrates. Comparing with mammalian, zebrafish, an evolutionarily distant vertebrate, contains 3 homologous ssat1 genes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In these vertebrates, the detoxification function of NV-AANAT might have been relegated to other enzymes (e.g., spermine/spermidine acetyltransferases) (48,49). From an evolutionary theoretical viewpoint, the history of the AANAT family is an interesting case of neofunctionalization (50); after a gene duplication, one of the copies evolves to assume a new function, and uncharacteristically, the other copy is lost rather than retaining the ancestral function.…”
Section: Discussionmentioning
confidence: 99%
“…In these vertebrates, the detoxification function of NV-AANAT might have been relegated to other enzymes (e.g., spermine/spermidine acetyltransferases) (48,49). From an evolutionary theoretical viewpoint, the history of the AANAT family is an interesting case of neofunctionalization (50); after a gene duplication, one of the copies evolves to assume a new function, and uncharacteristically, the other copy is lost rather than retaining the ancestral function.…”
Section: Discussionmentioning
confidence: 99%
“…SSAT1 is related to polyamine metabolism, whereas SSAT2 is not (Coleman et al, 2004;Vogel et al, 2006). In zebrafish, three ssat1 homologs, sat1a.1, sat1a.2 and sat1b, exist (Lien et al, 2013). We performed RT-PCR to investigate gene expression of three ssat1 genes in pigment cells and found that only sat1a.2 is expressed in melanophores and xanthophores (Fig.…”
Section: Visualization Of Cx394 In Vivo and In Vitromentioning
confidence: 99%
“…We identified 5 genes co-expressed with all the cart genes making a network of co-regulated genes with reduced expression after changes in feeding condition in only wild-type group. Among these genes, ckmt1 , sat1a.2 and arg2 have been shown to be expressed in the brain of zebrafish (Singh et al 2010 ; Drew et al 2012 ; Lien et al 2013 ) and mouse (Yu et al 2001 ; Yang et al 2008 ; Pfefferle et al 2011 ; St-Amand et al 2012 ). Ckmt1 encodes a creatine kinase required for the transfer of high energy phosphate from mitochondria to the cytosolic carrier (creatine), spermidine N1-acetyltransferase 1, sat1a.2 , encodes an enzyme involved in the catabolic pathway of polyamine metabolism, and arginase 2 encoded by arg2 is an enzyme catalysing the hydrolysis of arginine to ornithine and urea.…”
Section: Discussionmentioning
confidence: 99%